On the long-term variability of the green corona accordingly to four existing databases - Kobylinski, Z.; Baranska, A.; Ajabshirizadeh, A. (Кинематика и физика небесных тел, 2005)
We examine four long-term databases of monthly means of the whole disc green coronal brightness which cover the period of the last five and a half solar cycles to verify them, and compare their usefulness, as indices characterize the solar activity. We use the data from (1) the Norikura Observatory, (2) the Kislovodsk Observatory, (3) intensities detected by several coronographs and converted to the common photometric scale of Pic du Midi, (4) coronal indices obtained from detections of several observatories and converted to the photometric scale of Lomnicky Stit. We compare them by means of correlative analysis with the time series of sunspot numbers. The data (2) demonstrate the best agreement with sunspot number as the reference (r = 0.88).